2016
DOI: 10.1128/aac.02060-15
|View full text |Cite
|
Sign up to set email alerts
|

High Intracellular Concentrations of Posaconazole Do Not Impact on Functional Capacities of Human Polymorphonuclear Neutrophils and Monocyte-Derived Macrophages In Vitro

Abstract: Posaconazole is a commonly used antifungal for the prophylaxis and treatment of invasive fungal infections. We previously demonstrated that the intracellular concentration of posaconazole in peripheral blood mononuclear cells (PBMCs) and polymorphonuclear neutrophils (PMNs) was greatly increased compared to the plasma concentration. As these professional phagocytes are crucial to combat fungal infections, we set out to investigate if and how, beneficial or deleterious, this high loading of intracellular posaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(17 reference statements)
0
3
1
Order By: Relevance
“…In this study, the viability and chemotaxis of primary human neutrophils in vitro was preserved following exposure to posaconazole concentrations as high as 1.2 μg/mL (186). In contrast to our findings however, posaconazole-loaded primary human neutrophils did not exhibit enhanced killing of A. fumigatus conidia as determined by quantitative culture (186). It is likely that this observation reflects the fact that posaconazole is fungistatic rather than fungicidal.…”
Section: Introductioncontrasting
confidence: 97%
See 1 more Smart Citation
“…In this study, the viability and chemotaxis of primary human neutrophils in vitro was preserved following exposure to posaconazole concentrations as high as 1.2 μg/mL (186). In contrast to our findings however, posaconazole-loaded primary human neutrophils did not exhibit enhanced killing of A. fumigatus conidia as determined by quantitative culture (186). It is likely that this observation reflects the fact that posaconazole is fungistatic rather than fungicidal.…”
Section: Introductioncontrasting
confidence: 97%
“…Posaconazole is a broad-spectrum triazole that is highly active against (186). In this study, the viability and chemotaxis of primary human neutrophils in vitro was preserved following exposure to posaconazole concentrations as high as 1.2 μg/mL (186).…”
Section: Introductionmentioning
confidence: 89%
“…Previous researches revealed that inflammatory cells could serve as potential targets to achieve desirable efficacy during the treatments of tumor, microbial infection and inflammatory bone diseases. 55 , 56 , 57 , 58 Therefore, we consider that the treatment of Kin could be applied in the therapies of cancer, microbial infection and inflammatory diseases, which require future in-depth work.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that posaconazole accumulates in human peripheral blood mononuclear cells and polymorphonuclear leukocytes triggered an investigation on the impact of posaconazole-loaded leukocytes on the antifungal activity and functional capacity of different leukocytes [116][117][118][119]. High posaconazole intracellular concentrations did not show a significant impact on the functional capacities of human neutrophils and macrophages in vitro [117]. Natural killer cells also have proven to still be viable and they maintained their capacity under therapeutic concentrations of posaconazole [119].…”
Section: New Strategies For Posaconazole Targeted Therapymentioning
confidence: 99%